Immunoproteomic assay of Streptococcus suis serotype 2 isolated from patients - Kanruethai Wongsawan (2018)
Antigenic proteins of Streptococcus suis serotype 2 was investigated using an immunoproteomic technique. The whole cell proteins of two Streptococcus suis strains, LPH02 and MNCM43, isolated from patients with severe toxic shock syndrome and endocarditis were separated by two-dimensional gel electrophoresis (2-DE). Proteins were blotted onto nitrocellulose membrane. Immunodetection was done by individually incubating the membrane with either human serum from infected S. suis patients suffering from meningitis and septic shock or immunized rabbit serum. After excluding antigenic proteins found in serum of patients infected with closely related microorganisms Streptococcus spp., Staphylococcus spp. and Enterococcus spp., a total of 29 and 30 antigenic protein spots of LPH02 and MNCM43 strains were found, respectively. To compare the antigenicity between LPH02 and MNCM43 strains, the number of antigenic protein spots found by reacting with the same serum was considered. The antigenic protein patterns from different patient sera were also compared. Three specific antigenic protein spots were successfully identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS), which matched to o-acetylserine lyase, phosphomannose isomerase, and acyl-ACP thioesterase, respectively.